What does the urban historian owe to the anthropology and sociology? Experience from Łódź - Śmiechowski, Kamil (A mosaic city: The culture-oriented description, 2023)
The essay contains subjective reflection on the interconnections between the history of cities and anthropology and sociology, based on the author’s personal research experience, including research on the history of Łódź. According to the author, who in his career had episodes of close cooperation with both sociologists and cultural anthropologists, contemporary urban studies require close interdisciplinary cooperation. The author agrees with those historians and methodologists who criticise the too-rigid, idiographic approach to historical research. On the example of his own experience, he shows how inspiration from other sciences can improve the research workshop of a city historian and be an incentive to implement interdisciplinary research projects.